Relevansi Seruan Apostolik Christus Vivit dalam Kegiatan Toraja Youth Day 20205 - Octaviany Ursulin Wula; Pransiska Hiwi; Rensiska Paruri; Patrio Tandiangga (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2025)
Young Catholics have a very important role in the church. Young people are the next generation and are a pillar in building Spiritual faith, service, being the driving force and being the hope for the future development of the church. The purpose of this study is to analyze the relevance of the Apostolic Exhortation Christus Vivit in formulating and implementing Toraja Youth Day (TYD) 2025, a strategic activity of the Makassar Archdiocesan Youth Commission to empower Catholic Youth (OMK) in the Toraja Kevikepan. The method used is qualitative by means of interviews focusing on the Christus Vivit document and the context of organizing TYD 2025, including the challenges faced by OMK. The research shows that Christus Vivit's invitation to make young people protagonists, utilize creativity in proclaiming the Gospel, and the importance of contextual pastoral assistance are very relevant to the objectives of TYD 2025 to strengthen faith, build solidarity, and encourage active involvement of OMK. The integration of Christus Vivit values in TYD 2025, becomes a theological and pastoral foundation that inspires OMK to rise from the challenges of faith and witness as agents of change in the Church and in society.